2011
DOI: 10.4028/www.scientific.net/amr.197-198.947
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Antibacterial Ability of Silver-Loaded Maifanite

Abstract: Silver-loaded maifanite prepared at different particle sizes (60 mesh~200 mesh) and light calcining temperatures (100°C~800°C) of maifanite, different AgNO3solution concentrations (0.025 mol•L-1~0.300 mol•L-1) and pH values (2~7) were researched, simultaneously antibacterial ability of silver-loaded maifanite was investigated. Results indicate that the appropriate conditions of preparing silver-loaded maifanite are that particle size is 200 mesh, light calcining temperature is 100°C, AgNO3concentration is 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The result was in accordance with that of Yang et al . (2011), who reported that the main mineral diffraction peak position of maifanite did not change after calcining at 500 °C 45 . On the other hand, some peaks were disappeared and weakened a little after the modification treatment, which might be caused by the decrease of impurity after the modification treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The result was in accordance with that of Yang et al . (2011), who reported that the main mineral diffraction peak position of maifanite did not change after calcining at 500 °C 45 . On the other hand, some peaks were disappeared and weakened a little after the modification treatment, which might be caused by the decrease of impurity after the modification treatment.…”
Section: Resultsmentioning
confidence: 99%